PARTICLE ANALYSIS AND PREVENTION PLAN IN QUALITY ASSURANCE PROCESS OF OMEPRAZOLE FREEZE DRIED POWDER IN FACTORY X - Desyanto Raharjo I., Irwan
The visible particulate parameter is one of the quality aspects for injection products. Factory X has a problem regarding visible particles found in freeze dried Omeprazole powder made using the lyophilization process in a tray but not found in the lyophilization process in vials. Isolation of particles is carried out by filtering the reconstituted product using a 0.45 micron filter under Laminar Air Flow (LAF). Characterization of particles is carried out using particle identification paths listed on PDA TR 78. Based on testing using the Fourier Transform Infra Red (FTIR) spectrophotometer, the similarity with mannitol with a purity index of 0.9112 and 0.8446 towards omeprazole was obtained. Tests using X-Ray Difraction (XRD) showed a similarity with mannitol hemihydrate. Tests using the Scanning Electrone Microscope (SEM) show the particles look solid and there are no cavities that can help solubility. Based on the risk analysis carried out, the method / process aspect has a critical role in the formation of particles. The slow cooling rate causes the uneven cooling process and the formation of mannitol hydrate is thought to be a factor causing the formation of particles. The proposed strategy for handling visible particulates is a controlled nucleation process when freezing before annealing, preventing the formation of mannitol hemihydrate through the addition of sodium chloride into the formula to inhibit the crystallization process during the cooling process so as to prevent the appearance of mannitol hydrate, addition of annealing process with prolonged time, removal of mannitol hydrate through the secondary drying process with temperatures> 40 ° C and a vacuum pressure close to 0.000 mbar, and also change mannitol with other bulking agent. Another possible root cause is the interaction between omeprazole sodium with mannitol, but it was not explored in this final project.